Gene Architecture Facilitates Intron-Mediated Enhancement of Transcription - Dwyer, Katherine; Agarwal, Neha; Pile, Lori; Ansari, Athar (Frontiers in Molecular Biosciences, 2021)
Introns impact several vital aspects of eukaryotic organisms like proteomic plasticity, genomic stability, stress response and gene expression. A role for introns in the regulation of gene expression at the level of transcription has been known for more than thirty years. The molecular basis underlying the phenomenon, however, is still not entirely clear. An important clue came from studies performed in budding yeast that indicate that the presence of an intron within a gene results in formation of a multi-looped gene architecture. When looping is defective, these interactions are abolished, and there is no enhancement of transcription despite normal splicing. In this review, we highlight several potential mechanisms through which looping interactions may enhance transcription. The promoter-5' splice site interaction can facilitate initiation of transcription, the terminator-3' splice site interaction can enable efficient termination of transcription, while the promoter-terminator interaction can enhance promoter directionality and expedite reinitiation of transcription. Like yeast, mammalian genes also exhibit an intragenic interaction of the promoter with the gene body, especially exons. Such promoter-exon interactions may be responsible for splicing-dependent transcriptional regulation. Thus, the splicing-facilitated changes in gene architecture may play a critical role in regulation of transcription in yeast as well as in higher eukaryotes.